PENGARUH PENGALAMAN MENGAJAR TERHADAP PROFESIONALISME GURU PRODUKTIF DI SMK NEGERI 2 KUPANG - Edyan, Roly; Ketut M. Kuswara; Samuel Tangis; Asrial (Jurnal Lazuardi, 2025)
This study aims to determine the influence of teaching experience on the professionalism of vocational subject teachers at SMK Negeri 2 Kupang. Productive teachers play a crucial role in improving the quality of vocational school graduates, as they teach practical subjects closely aligned with industry needs. This research used a quantitative approach and involved 21 respondents from the property construction and geospatial geomatics departments. Data were collected through a closed-ended questionnaire and analyzed using simple linear regression. The results indicate that teaching experience has a positive and significant effect on teacher professionalism. Teachers with longer teaching experience tend to demonstrate stronger pedagogical skills, better subject mastery, and higher involvement in professional development and the use of educational technology. These findings suggest that experience is not merely a matter of duration, but also reflects the quality of a teacher’s engagement in improving the learning process. Therefore, it is essential for schools and policymakers to support teacher career development through continuous training and targeted professional development policies. Furthermore, the results show that both teaching experience and teacher professionalism are at a very high level, with empirical mean scores of 39.95 (61.9% of the theoretical score) and 172.05 (66.7% of the theoretical score), respectively. The positive influence was confirmed by an F-test result of 16.028 with a significance level of 0.001 (< 0.05), and a t-test result where the calculated t-value of 4.004 exceeds the critical t-table value of 1.735. The coefficient of determination (R²) was 0.457, indicating that 45.7% of the variation in teacher professionalism is influenced by teaching experience, while the remaining 54.3% is affected by other factors. Thus, teaching experience is proven to significantly affect the professionalism of productive teachers.